What is the range of the function f(x) = -|X - 4| + 5?
19 A. (-0,5)
B. (-09. 5)
C. (-5. infinity)
D. (5 .infinity)​

Answers

Answer 1

Answer:

Range = (-∞, 5)

Step-by-step explanation:

This is the absolute value function with transformation.

The parent function is f(x) = |x|

This function has a "negative" in front, so it makes it reflect about x axis

The -4 after x makes horizontal translation of 4 units right

the +5 at the end makes the function translate 5 units UP

The graph is shown in the attached picture.

Looking at the graph, we can clearly see the range. The range is the allowed y-values. Hence, we can see that the range is  -infinity to 5

answer is not properly given, so i can't choose from the options, but the answer is -∞, 5 to 5

What Is The Range Of The Function F(x) = -|X - 4| + 5?19 A. (-0,5)B. (-09. 5)C. (-5. Infinity)D. (5 .infinity)

Related Questions

Select the correct answer from each drop-down menu. The base of pyramid A is a rectangle with a length of 10 meters and a width of 20 meters. The base of pyramid B is a square with 10-meter sides. The heights of the pyramids are the same. The volume of pyramid A is the volume of pyramid B. If the height of pyramid B increases to twice that of pyramid A, the new volume of pyramid B is the volume of pyramid A.

Answers

Step-by-step explanation:

The formula of a volume of a pyramid:

[tex]V=\dfrac{1}{3}BH[/tex]

B - base area

H - height

H - height of pyramids

Pyramid A:

[tex]B=(10)(2)=200\ m^2[/tex]

[tex]V_A=\dfrac{1}{3}(200)H=\dfrac{200}{3}H\ m^3[/tex]

Pyramid B:

[tex]B=10^2=100\ m^2[/tex]

[tex]V_B=\dfraC{1}{3}(100)H=\dfrac{100}{3}H\ m^3[/tex]

[tex]V_A>V_B\\\\V_A=2V_B[/tex]

The volume of the pyramid A is twice as large as the volume of the pyramid B.

The new height of pyramid B: 2H

The new volume:

[tex]V_{B'}=\dfrac{1}{3}(100)(2H)=\dfrac{200}{3}H\ m^3[/tex]

The volume of the pyramid A is equal to the volume of the pyramid B.

To compare the volumes of the two pyramids, we first need to calculate the volume of each pyramid using the formula for the volume of a pyramid:
\[ V = \frac{1}{3}Bh \]
where \( V \) is the volume, \( B \) is the area of the base, and \( h \) is the height.
First, let's calculate the volume of pyramid A:
\[ \text{Area of base of pyramid A} = \text{length} \times \text{width} = 10 \, \text{meters} \times 20 \, \text{meters} = 200 \, \text{square meters} \]
Now, let's call the height of pyramid A (and originally pyramid B) \( h \). Then, the volume of pyramid A is:
\[ V_{\text{A}} = \frac{1}{3} \times 200 \, \text{m}^2 \times h = \frac{200h}{3} \, \text{cubic meters} \]
Next, let's calculate the volume of pyramid B with its original height \( h \):
\[ \text{Area of base of pyramid B} = \text{side} \times \text{side} = 10 \, \text{meters} \times 10 \, \text{meters} = 100 \, \text{square meters} \]
So the original volume of pyramid B is:
\[ V_{\text{B}} = \frac{1}{3} \times 100 \, \text{m}^2 \times h = \frac{100h}{3} \, \text{cubic meters} \]
Now we can compare the volumes of pyramid A and the original volume of pyramid B:
\[ \frac{V_{\text{A}}}{V_{\text{B}}} = \frac{\frac{200h}{3}}{\frac{100h}{3}} = \frac{200}{100} = 2 \]
So, pyramid A has twice the volume of pyramid B.
Now, if the height of pyramid B increases to twice that of pyramid A, its new height is \( 2h \). Therefore, the new volume of pyramid B is:
\[ V_{\text{B new}} = \frac{1}{3} \times 100 \, \text{m}^2 \times 2h = \frac{200h}{3} \, \text{cubic meters} \]
Comparing this new volume of pyramid B to the volume of pyramid A:
\[ \frac{V_{\text{B new}}}{V_{\text{A}}} = \frac{\frac{200h}{3}}{\frac{200h}{3}} = 1 \]
So, the new volume of pyramid B is equal to the volume of pyramid A.
In summary, the volume of pyramid A is twice the volume of pyramid B when their heights are the same. If the height of pyramid B increases to twice that of pyramid A, the new volume of pyramid B is equal to the volume of pyramid A.

A toy plush weighed one- sixth of a pound. A flimsy box can hold 4 pounds. How many toy plushes could the box hold?

Answers

Answer:

24 plushies

Step-by-step explanation:

1 pound = 6 toy plushies

6(4)=24

PLZ HELP, WILL GIVE BRAINLIEST
What is the value of x?



A.
73°
B.
45°
C.
35°
D.
25°

Answers

Answer:

x = 35

Step-by-step explanation:

The sum of the 3 angles in a triangle = 180°

Subtract the sum of the 2 base angles from 180 for angle at vertex

vertex = 180° - (73 + 51)° = 180° - 124° = 56°

The vertex angle is composed of x and 21, so

x + 21 = 56 ( subtract 21 from both sides )

x = 35

Rip van Winkle fell asleep for a very long time. When he fell asleep, his beard was 8 millimeters long, and each passing week it grew 2 additional millimeters.
Graph the length of Rip van Winkle's beard (in millimeters) as a function of time (in weeks).

Please help me to understand how to graph this problem.

Answers

A function that models the situation is f(x) = 2x + 8.

A graph of the length of Rip van Winkle's beard (in millimeters) as a function of time (in weeks) is shown in the picture below.

In Mathematics, the slope-intercept form of the equation of a straight line refers to the general equation of a linear function and it is represented by this mathematical equation;

y = mx + b

where:

m represents the slope.x and y are the points.b represents the y-intercept or initial value.

Since Rip van Winkle's beard was 8 millimeters long when he fell asleep, and each passing week it grew 2 additional millimeters, we can logically deduce the following parameters;

slope, m = 2.

initial value or y-intercept, b = 8.

In this context, an equation for the function that relates the length of his beard (in millimeters) to time (in weeks) can be written as follows;

y = mx + b

f(x) = 2x + 8

Is 24/40= 4/8 true proportion?

Answers

Answer:

No, that is not the true proportion.

Step-by-step explanation:

40 divided by 8 is 5. 5 multiplied by 4 is 20. Therefore, the true proportion would be 20/40 = 4/8.

$1334 is deposited into a savings account at 8% interest, compounded quarterly. To the nearest year, how long will it take for the account balance to reach $1,000,000?

Answers

Answer:

  84 years

Step-by-step explanation:

The future value of an investment is given by ...

  FV = P(1 +r/n)^(nt)

where P is the principal amount, r is the annual rate, and n is the number of times per year interest is compounded. Filling in the given values and solving for t, we get ...

  1000000 = 1334(1 +.08/4)^(4t)

  749.6252 ≈ 1.02^(4t) . . . . divide by 1334 and simplify

  log(749.6252) ≈ 4t·log(1.02) . . . . take logarithms

  t ≈ log(749.6252)/(4·log(1.02)) ≈ 83.57

It will take about 84 years for the account balance to reach $1,000,000.

Alex and his father took a taxi cab that charges $2.60 per mile plus $1.50 for each passenger, and they paid a total of $18.60. Alex wrote the equation 18.60=2.60b+3 for this situation and found b=6. Which statement is true about the solution b=6?

Answers

Answer:

The solution b=6 tells us that Alex and his father traveled 6 miles on the taxi

Step-by-step explanation:

Given

18.60=2.60b+3

Here 18.60 is the total amount paid, 2.60 is the rate per mile and 3 is the charges for two passengers.

The solution b=6 tells us that Alex and his father traveled 6 miles on the taxi i.e. b represents miles ..

the answer is: the solution b = 6 gives the number of miles the taxi traveled.

i just did the workbook :)

Subtract. 5x^2-5x+1-(2x^2+9x-6)

Answers

Hello!

The answer is:

[tex]3x^{2} -14x+7[/tex]

Why?

To solve the problem we need to add/subtract like terms. We need to remember that like terms are the terms that share the same variable and the same exponent.

For example, we have:

[tex]x^{2} +2x+3x=x^{2} +(2x+3x)=x^{2}+5x[/tex]

We have that we were able to add just the terms that were sharing the same variable and exponenr (x for this case).

So, we are given the expression:

[tex]5x^2-5x+1-(2x^2+9x-6)=5x^{2}-2x^{2}-5x-9x+1-(-6)\\\\(5x^{2}-2x^{2})+(-5x-9x)+(1-(-6))=3x^{2}-14x+7[/tex]

Hence, the answer is:

[tex]3x^{2} -14x+7[/tex]

Have a nice day!

What is the ratio of 102 steps walked in 1 minute?

Answers

Answer:

102 steps/1minute

In seconds it would be 102/60 which can be reduced to 17/10, or 1.7

Help please and fast

Answers

Answer:

b. 7/16

Step-by-step explanation:

We can see in the figure that the total dimension parallel to C is 15/16.

The other half dimension with c is 1/2

We will get the dimension C by subtracting 1/2 from 15/16

So,

C = 15/16 - 1/2

= (15-8)/16

=7/16

So the dimension C is 7/16.

Hence option b is correct ..

A = B/2 = C/5 a:b:c=?

Answers

Answer:

[tex]\large\boxed{A:B:C=\dfrac{1}{10A}}[/tex]

Step-by-step explanation:

[tex]A=\dfrac{B}{2}=\dfrac{C}{5}\\\\A=\dfrac{B}{2}\qquad\text{multiply both sides by 2}\\\\2A=B\to\boxed{B=2A}\\\\A=\dfrac{C}{5}\qquad\text{multiply both sides by 5}\\\\5A=C\to C=5A\\\\A:B:C=A:2A:5A=1:2:5A=\dfrac{1}{2}:5A=\dfrac{1}{2}\cdot\dfrac{1}{5A}=\dfrac{1}{10A}[/tex]

m2 - 36 = 0

Several solutions please

Answers

Answer:

m = ±6

Step-by-step explanation:

m^2 -36 =0

Add 36 to each side

m^2-36 +36 = 0+36

m^2 = 36

Take the square root of each side

sqrt(m^2) = ±sqrt(36)

m = ±6

Answer:+6 or -6

Step-by-step explanation:m^2 - 6^2

it becomes difference of two squares,

(m+6) (m-6)=0

m-6=0,m=6

m+6=0,m=-6


55. If 3x = 4y, the value of (x + y)^2 : (x - y)^2 is:

Answers

Answer:

[tex]\large\boxed{(x+y)^2:(x-y)^2=49}[/tex]

Step-by-step explanation:

[tex]3x=4y\qquad\text{subtract}\ 3y\ \text{from both sides}\\\\3x-3y=y\qquad\text{distributive}\\\\3(x-y)=y\qquad\text{divide both sides by 3}\\\\x-y=\dfrac{y}{3}\qquad(*)\\------------------\\3x=4y\qquad\text{add}\ 3y\ \text{to both sides}\\\\3x+3y=7y\qquad\text{distributive}\\\\3(x+y)=7y\qquad\text{divide both sides by 3}\\\\x+y=\dfrac{7y}{3}\qquad(**)\\------------------[/tex]

[tex](x+y)^2:(x-y)^2=\dfrac{(x+y)^2}{(x-y)^2}\qquad\text{use}\ \left(\dfrac{a}{b}\right)^n=\dfrac{a^n}{b^n}\\\\=\left(\dfrac{x+y}{x-y}\right)^2\qquad\text{substitute}\ (*)\ \text{and}\ (**)\\\\=\left(\dfrac{\frac{7y}{3}}{\frac{y}{3}}\right)^2=\left(\dfrac{7y}{3}\cdot\dfrac{3}{y}\right)^2\qquad\text{cancel}\ 3\ \text{and}\ y\\\\=(7)^2=49[/tex]

Nat bought 3 colas for $1.25 each, 2 hot-dogs for $2.50 each, and a hamburger for $6.50. He paid with $20 bill. How much money does Nat have left?

Answers

Answer:

$4.75 is how much money is left over

Step-by-step explanation:

3* 1.25= 3.75

2* 2.50= 5.00

1* 6.50+ 6.50

5.00+3.75+6.50= 15.25

20- 15.25= 4.75

Final answer:

Nat spent a total of $15.25 on colas, hot dogs, and a hamburger. After paying with a $20 bill, he has $4.75 left.

Explanation:

To calculate how much money Nat has left after his purchases, we will add up the cost of the items he bought and subtract that total from the $20 bill he used for payment.

Cost of 3 colas: 3 × $1.25 each = $3.75

Cost of 2 hot-dogs: 2 × $2.50 each = $5.00

Cost of 1 hamburger: $6.50

Now we'll sum these amounts to find the total spending:

Total spending = $3.75 + $5.00 + $6.50 = $15.25

Next, we subtract the total spending from the $20 bill:

Change = $20.00 - $15.25 = $4.75

Therefore, Nat has $4.75 left after his purchase.

If ELF is congruent to GJH, EF=12 and LF=7.8 find IJ. Round answer to the hundredths place. A. 4.78 B 5.62 C 4.98 D 5.07

Answers

EF = 12

KF = 6

LF = 7.8

LK = sqrt(7.8^2-6^2) = 4.98

IJ = LK

Answer with explanation:

→ΔELF ≅ Δ GHJ-------[Given]

→EF=GH----------[CPCT]

→GJ=FL-------[CPCT]

Let , O be the center of the circle.

→ EK=KF--------[Perpendicular from the center to the chord bisects the chord.]

→GI=IH------[Reason same as Above]

→→EK=GI, KF=HI

→→OJ=OL

→OK=KI

→OJ-OK=OL-KI

→LK=IJ

⇒→Δ LKF ≅ Δ JIG-------[SAS]

Now, In Δ LKF, By Pythagorean Theorem

 →(LF)²=(LK)²+(KF)²

→(7.8)²=(LK)²+(6)²

→60.84-36=(LK)²

→24.84=(LK)²

LK=4.98

→→LK=IJ=4.98

Option C:→4.98

Follow the steps and finish the solution.
7(x-3) = 28
Distributive property
7x-21 = 28
Addition property of equality
7x = 49
Division property of equality
X
=
What is the value of x?
07
O 42
O 56
Mark this and return
Save and Exit
Save and Exit
Next
Next
Submit

Answers

Answer:

x=7

Step-by-step explanation:

7(x-3) = 28

Distributive property

7x-21 = 28

Addition property of equality

7x = 49

Division property of equality

7x/7 = 49/7

x = 7

The value of x is 7 ..

Answer:

7

Step-by-step explanation:

The apother is 4 m and a side is 5.8 m. What is the area
of the pentagon? Round to the nearest whole number.

Answers

Answer:

58 m^2.

Step-by-step explanation:

The  area of one of the 5 triangles is:

1/2 * 5.8 * 4 = 11.6 m^2

So the area of the pentagon

= 5 + 11.6

= 58 m^2

Answer:

The area is 58 meters squared.

Step-by-step explanation:

Since the pentagon is conveniently split into 5 separate but equal triangles, we only need to find the area of 1 triangle to find the rest. The area of triangles, as I'm sure you know, is 1/2bh. Using this equation, we get (1/2)x4x5.8. This equals 11.6. This is the area of one of the triangles. There are 5 triangles, so we multiply the area of 1 triangle by 5. 11.6x5= 58 meters squared. Hope this helped. :)

what is the solution to x=√3x+10?

Answers

Answer:

x=5

Step-by-step explanation:

Given

[tex]x=\sqrt{3x+10}[/tex]

Squaring on both sides

[tex]x^2=(\sqrt{3x+10})^2 \\x^2=3x+10\\x^2-3x-10 = 0\\x^2-5x+2x-10 = 0\\x(x-5)+2(x-5) = 0\\(x-5)(x+2)=0\\x=5\\and\\x=-2[/tex]

Since putting -2 gives us:

[tex]-2=\sqrt{3(-2)+10} \\-2=\sqrt{-6+10}\\-2=\sqrt{4}\\-2\neq 2[/tex]

2 is an extraneous solution.

Therefore, the solution to x=√3x+10 is x=5 ..

simplify the following fraction (9/16/1/4)-1/5

Answers

Answer: [tex]\frac{41}{20}[/tex]

Step-by-step explanation:

The first step is to make the division of the fractions [tex]\frac{9}{16}[/tex] and

[tex]\frac{1}{4}[/tex]. To do this, you can flip the fraction [tex]\frac{1}{4}[/tex] over and multiply the numerators and the denominators of the fractions. Then:

[tex](\frac{\frac{9}{16}}{\frac{1}{4}})-\frac{1}{5}=(\frac{9}{16}*4)-\frac{1}{5}=\frac{36}{16}-\frac{1}{5}[/tex]

Reduce the fraction [tex]\frac{36}{16}[/tex]:

 [tex]=\frac{9}{4}-\frac{1}{5}[/tex]

Now you can make the subtraction:  in this case the Least Common Denominator (LCD) will be the multiplication of the denominators.   Divide each denominator by the LCD and multiply this quotient by the corresponding numerator and then subtract the products. Therefore you get:

[tex]=\frac{45-4}{20}=\frac{41}{20}[/tex]

helppppppppppppppppppppping

Answers

Answer:

B

Step-by-step explanation:

First we simplify the equation:

3y − 2x = k (5x − 4) + 6

3y − 2x = 5k x − 4k + 6

3y = (5k + 2) x − 4k + 6

y = (5k + 2)/3 x + (6 − 4k)/3

The line has a positive slope and negative y-intercept.  So:

(5k + 2)/3 > 0

(6 − 4k)/3 < 0

Solving for k in each:

k > -2/5

k > 3/2

k must be greater than -2/5 and 3/2.  Since 3/2 is already greater than -2/5, then k must be greater than 3/2.

If k > 3/2, then it's also true that k > 0.  So the answer is B.

1.
1400
Simplify: -
Show your work.

Answers

Answer:

1400

Step-by-step explanation:

Nothing can be done further. If I saw the rest of the question, I would be capable of assisting you.

I am joyous to assist you.

Two lines and a transversal form corresponding angles that are congruent. Describe the two lines

Answers

Answer:

parallel

Step-by-step explanation:

If you have two lines and a transversal that form corresponding angles that are congruent. Then the alternate interior angles are congruent and the same-side interior (some people call these consecutive angles) are supplementary.

This has to deal with Parallel Lines Theorem or the Converse of Parallel Lines Theorem.

The lines would be parallel.

Two lines will be parallel.

What is corresponding angle?

When two lines are cut by a transversal then the angles formed relatively same position in their respective line at the intersection transversal and two lines are called corresponding angles.

What is converse of corresponding angles theorem?

Converse of corresponding angles theorem states that When two lines are cut by a transversal and the formed corresponding angles are congruent then the two lines will be parallel.

Here given that two lines and transversal are forming corresponding angles which are congruent. So by converse of corresponding angles theorem, the two lines will be parallel to each other.

Therefore two lines will be parallel.

Learn more about corresponding angle

here: https://brainly.com/question/2496440

#SPJ2

HELP!!!! PLEASE need help now its an emergency.

Answers

Answer:

121,6

Step-by-step explanation:

Since the only difference between the triangles are the letters and a few missing numbers, just replace the letters to get your answer. A and D are the same B and E are the same and C and F are the same. So the measurement of angle A is 121 degrees and the length of AB is 6

The length of a rectangle is three times its width, and its area is 9 cm2

. Find the

dimensions of the rectangle.​

Answers

Answer:

3√3 cm. = l

√3 cm. = w

Step-by-step explanation:

l = 3w

9 = 3w[w] ↷

9 = 3w² [Divide by 3]

3 = w² [Take the square root]

√3 = w [plug this back into the top equation to get a length of 3√3 cm.]

I am joyous to assist you anytime.

f(x) = -x^3 + 3x^2 + x - 3 Using the end behavior of f(x), determine the graph of the function

Answers

Answer:

Here, the given function,

[tex]f(x) = -x^3 + 3x^2 + x - 3[/tex]

Since, the leading coefficient is negative, and degree is odd,

Thus, the end behaviour of the function is,

[tex]f(x)\rightarrow \infty\text{ as }x\rightarrow -\infty[/tex]

[tex]f(x)\rightarrow -\infty\text{ as }x\rightarrow \infty[/tex]

Therefore, the graph rises to the left and falls to the right.

Now, when f(x) = 0

[tex]-x^3+3x^2+x-3=0[/tex]

[tex]\implies -(x-3)(x-1)(x+1)=0[/tex]

[tex]\implies x=3, 1, -1[/tex]

That is, graph intercepts the x-axis at (3, 0), (1, 0) and (-1, 0).

When x = 0,

[tex]f(x) = - 3[/tex]

That is, graph intersects the y-axis at ( 0, -3),

Also, for 0 > x > -1 , f(x) is decreasing,

For 2.55 > x > 0, f(x) is increasing,

For 3 > x > 2.55, f(x) is decreasing,

Hence, by the above explanation we can plot the graph of the function ( shown below )

Answer:w

Step-by-step explanation: it should be w i got it on plato

how do I solve this: 9b less than 40

Answers

Answer:

b < 4.44

Step-by-step explanation:

This is an inequality.

The sign for 'less than' is '< '

Write 9b less than 40 in inequality form.

9b < 40 (Take 9 on the other side of the inequality and divide it by 40)

b < 40/9

b < 4.44

!!

Rodney is given two linear equations: x – y = 11 and 2x + y = 19. What value of x should he get as a solution for this system of linear equations

Answers

Answer:

x = 10

Step-by-step explanation:

Given the 2 equations

x - y = 11 → (1)

2x + y = 19 → (2)

Adding the 2 equations term by term eliminates the term in y, that is

(x + 2x) + (- y + y) = (11 + 19), simplifying gives

3x = 30 ( divide both sides by 3 )

x = 10

Answer:

x = 10

Step-by-step explanation:

We know that Rodney is given the following two linear equations and we are to find the value of x at which he would get a solution for this system of linear equations:

[tex] x - y = 1 1 [/tex] - (1)

[tex] 2 x + y = 1 9 [/tex] - (2)

From (1):

[tex]x=11+y[/tex]

Substituting this value of x in (2):

[tex]2(11+y)+y=19[/tex]

[tex]22+2y+y=19[/tex]

[tex]3y=19-22[/tex]

[tex]y=-\frac{3}{3}[/tex]

[tex]y=-1[/tex]

Substituting this value of y in (1) to find x:

[tex]x=11+(-1)[/tex]

x = 10

Given the function f(x)=-5x^2-x+20 find f(3)

Answers

Answer:

-28

Step-by-step explanation:

-5(3)^2 - 3 + 20

-5*9 - 3 + 20

-45 -3+ 20

-48+ 20

-28

Hope it helps!

Solve the system of equations and choose the correct answer from the list of options. (4 points)

x − y = 7
y = 3x + 12


2 over 19 comma 2 over 33


negative 2 over 19 comma negative 33 over 2


negative 19 over 2 comma negative 33 over 2


19 over 2 comma 33 over 2


Answers

Answer:

x=-19/2  y=-33/2

Step-by-step explanation:

x − y = 7

y = 3x + 12

Substituting the second equation into the first

x − (3x+12) = 7

Distribute the minus sign

x-3x-12 = 7

Combine like terms

-2x-12 =7

Add 12 to each sid

-2x-12+12 =7+12

-2x=19

Divide each side by -2

-2x/-2 = 19/-2

x = -19/2

Now we need to find y

y = 3x+12

y = 3(-19/2) +12

y = -57/2 +24/2

y = -33/2

Answer:

(-19/2, -33/2)

Step-by-step explanation:

using the rate of Rs. 124.40 per using US dollar, find the US dollar for Rs. 158610.​

Answers

Answer:

1275 USD

Step-by-step explanation:

124.40 Rs -----> 1 USD

158610 Rs -----> x USD

124.40x=158610

×=158610/124.40

x=1275 USD

Other Questions
cos x cos (-x) -sin x sin (-x) = 1. Verify the Identity. Please Show All Steps. What is Grave's disease? What is an example of a linear actuator? 2(5x+3)=4x+18 how would i solve this problem the probability of picking rotten apple in a box is 1/100 .if there are 6 boxes containing 1200 apples each how many rotten apple may be picked Find the x-intercept of the line whose equation is 8x+2y=4 Madison represented the sentence "The product of 3 and the difference of -4 and the quotient of a number and -2 is at most 5" by using the inequality 3 (-4 - n/-2) < 5What is madison's error? Gold Company was experiencing financial difficulties, but was not bankrupt or insolvent. The National Bank, which held a mortgage on other real estate owned by Gold, reduced the principal from $110,000 to $85,000. The bank had made the loan to Gold when it purchased the real estate from Silver, Inc. Pink, Inc., the holder of a mortgage on Golds building, agreed to accept $40,000 in full payment of the $55,000 due. Pink had sold the building to Gold for $150,000 that was to be paid in installments over 8 years. As a result of the above, Gold must:a.Include $40,000 in gross income.b.Reduce the basis in its assets by $40,000.c.Include $25,000 in gross income and reduce its basis in its assets by $15,000.d.Include $15,000 in gross income and reduce its basis in the building by $25,000.e.None of these. Find the measure of stv in the figure Which would be an adaptation in a rain forest, but not in a desert? A. Ability to store water for a long time B. Better eyes for hunting prey C. Skin that blends in with green plants D. Very small leaves to trap water cos4theta+cos2theta/ cos4theta-cos2theta= _____-cot3cot-2cot3cotcot6cot2-1 Calcium hydroxide is a strong base but is not very soluble ( Ksp = 5.02 X 10-6 ). What is the pH of a saturated solution of Ca(OH)2 ? A 0.8 g object is placed in a 534 N/C uniform electric field. Upon being released from rest, it moves 12 m in 1.2 s. Determine the object's acceleration & charge magnitude. Assume the acceleration is due to the E-field (i.e., ignore all other forces). What belief system was the basis for both christianity and islam? Over time, some plants growing in an area are crowded out by other plants. The new plants use up water and nutrients needed by the previous plants. The disappearance of the first plants is due to: Where is the origin of the rectus femoris? Three consecutive integers have a sum of 21. Which equation can be used to find the value of the three numbers?x+x+x=-21x+2x+3x=-21x+(x+1)+(x+2)=-21x+(x+2)+(x+4)=-21 Which type of modulation is applied to radio-controlled toys? What type of tissue is housed in the appendix? What is appendicits? How can appendicitis lead to peritonitis Which of the following is the simplified fraction that's equivalent to 9.315? A. 9315999 B. 93199 C. 9105333 D. 935111